Protective Effects of Garlic and Cinnamon Oils on Hepatocellular Carcinoma in Albino Rats - Salah M. Aly; Hamdy A. Fetaih; Abeer A. I. Hassanin; Mosleh M. Abomughaid; Aliaa A. Ismail (Analytical Cellular Pathology)
Natural oils are traditional medicinal herbs, which have attracted interests for its potential anti-inflammatory and anticancer activities. The present work is aimed at evaluating the protective effect of garlic oil and cinnamon oil on diethylnitrosamine- (DENA-) and 2-acetylaminofluorene- (2-AAF-) induced p53 gene mutation and hepatocarcinogenesis in rats. Forty male albino rats were divided into 4 equal groups: control, hepatocellular carcinoma (HCC), garlic oil-HCC, and cinnamon oil-HCC. The HCC-induced group showed a significant decrease in the body mass and a significant elevation in the liver weight, alpha-fetoprotein (AFP), liver enzymes, hepatic malondialdehyde (MDA), and p53 protein expression levels as well as genetic mutations in intron 5 of p53 gene in the form of Single-Nucleotide Polymorphisms (SNPs) and insertions. In addition, the glutathione (GSH) level and superoxide dismutase (SOD) activities were increased. While HCC rats pretreated with garlic oil or cinnamon oil were significantly reversed, these destructive actions increased GSH and SOD levels. The HCC-induced group showed histopathological features of liver cancer including hypercellularity, nuclear hyperchromasia, mitotic figures, and preneoplastic foci. On the other hand, HCC rats pretreated with garlic oil or cinnamon oil revealed partial reversal of normal liver architecture. The present findings proposed that these natural oils have the ability to improve liver function, significantly reduced the liver toxicity and HCC development. However, further sophisticated studies are recommended before their use as conventional therapeutics for HCC treatment.